The impact of a short-term digital marketing campaign on improving the sales of hotel capacities - Cimbaljević, Marija; Dunjić, Milosav (Turizam, 2022)
This paper aims to present an example of an active approach to the use of social networks as a part of marketing activities, to stimulate short-term capacity sales in specific terms. The subject of the research is the influence of a specific online marketing campaign through selected social networks on the improvement of the sales of accommodation capacities with the example of the hotel Putnik on Kopaonik. The goal of the campaign is to find a quick way to potential users and to encourage their interest. It is of great importance to plan and direct the marketing campaign because the wide distribution does not directly affect the results. Online marketing has shown to be a useful tool for fast group targeting to which the offer will be directed. The research aims to present preliminary short-term results of social media marketing activities on increasing capacity utilization and achieving higher business results. The data used in the paper are unpublished, acquired from the official business report of the hotel software "PROTEL".